Visiting research fellow at Abu Dhabi University, United Arab Emirates - UiTM, Fakulti Sains Gunaan (Faculty of Applied Sciences, 2020)
Dr. Abdel-Baset M. A. Ibrahim had successfully secured a position as a Visiting Research Fellow at the Department of Applied Sciences and Mathematics, College of Arts and Sciences, Abu Dhabi University (ADU). The program is initiated by ADU to enable their researchers to jointly work with international researchers to contribute to nationally and regionally relevant areas of research. The programme allows established researchers to join ADU as Visiting Fellows or Senior Visiting Fellows based on the needs of individual projects. Candidates are expected to be accomplished researchers publishing at the highest level in their fields. They should also have experience in supporting the development of less experienced researchers and working in teams. Joint publications and collaborative research programmes with ADU researchers are the key outcomes of this initiative. The collaboration aims to build productive teams comprising of international research experts and ADU researchers as well as cultivate fruitful transfer and sharing of knowledge to benefit both parties. Based on performance, the Fellowships may be extended.